Isolasi dan Identifikasi Bakteri Asam Laktat dari Cairan Rumen Sapi Bali sebagai Kandidat Biopreservatif ISOLATION AND IDENTIFICATION OF ACID LACTIC BACTERIA FROM BALI CATTLE’S GASTRIC FLUID AS A POTENTIAL CANDIDATE OF BIOPRESERVATIVE - Suardana, I Wayan; Suarsana, I Nyoman; Sujaya, I Nengah; Wiryawan, Komang Gede (Jurnal Veteriner; Vol 8 No 4 (2007))
A study was conducted to isolate and identify of lactic acid bacteria originated from gastric fluid of bali cattle, and to determine their potential as the candidates of biopreservative. Lactic acid bacteria were isolated by culturing the gastric fluid of bali cattle in de Mann, Rogosa, Sharpe (MRS) medium; screening the bacteria, and identification of bacteria species by Analytical Profile Index (API) 50 CHL Kit. The results showed that, the new species of lactic acid bacteria were isolated and identified as Lactococcus lactis spp lactis 1 (SR21 isolate) and Lactobacillus brevis 1 (SR54 isolate) that have broad spectrum antimicrobial activities. It is clear from this study that a potential lactic acid bacteria producing antimicrobial agent can be isolated from the gastric fluid of bali cattle.
Keywords: lactic acid bacteria, bali cattle’s gastric fluid, biopreservatives